1985
DOI: 10.1128/mcb.5.5.923
|View full text |Cite
|
Sign up to set email alerts
|

Membrane mutants of animal cells: rapid identification of those with a primary defect in glycosylation.

Abstract: Membrane mutants of animal cells have been isolated by several laboratories, using a variety of selection protocols. The majority are lectin receptor mutants arising from altered glycosylation of membrane molecules. They have been obtained by selection for resistance to cytotoxic plant lectins or by alternative protocols designed, in many cases, to isolate different classes of receptor mutants. The identification of most membrane mutants expressing altered surface carbohydrates is rapidly achieved by determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 39 publications
1
43
0
1
Order By: Relevance
“…The Lec1 CHO cell line lacks N-acetylglucosaminyltransferase I, the enzyme responsible for the committed step in the reelaboration and diversification of carbohydrates in the glycosylation pathway (18,26,27). Therefore, Lec1 cells are unable to synthesize complex-type N-linked oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…The Lec1 CHO cell line lacks N-acetylglucosaminyltransferase I, the enzyme responsible for the committed step in the reelaboration and diversification of carbohydrates in the glycosylation pathway (18,26,27). Therefore, Lec1 cells are unable to synthesize complex-type N-linked oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Transport of UDP-galactose into Golgi vesicles from these cells was 90% defective compared to vesicles from wild-type cells, whereas transport of other nucleotide sugars, including uridine derivatives and CMP-sialic acid, was normal (25). Biochemical studies had previously shown that the resulting phenotype was not due to an impairment in the biosynthesis of nucleotide sugars, glycosyltransferases, or macromolecular and lipid acceptors (37,(77)(78)(79).…”
Section: Phenotype Of Mutants Defective In Transport Of Nucleotide Sumentioning
confidence: 99%
“…These mutants were isolated because of their resistance to plant lectins. CHO Lec8 (77,78), CHO clone 13 (78), and MDCK II-RCA R (37) belong to the same genetic complementation group. They have a 70-90% deficiency of galactose in their glycoproteins, glycosphingolipids, and selective proteoglycans.…”
Section: Phenotype Of Mutants Defective In Transport Of Nucleotide Sumentioning
confidence: 99%
“…The ␤ 1 subunit is also heavily glycosylated, with four potential Nglycosylation motifs within its extracellular N-terminal domain (24). To determine whether the observed isoform-specific shifts in Na v gating produced by ␤ 1 are caused by ␤ 1 sialic acids, we co-expressed each of the ␣ subunits with ␤ 1 in two well characterized CHO cell lines that produce proteins with differing amounts of attached sialic acids (41)(42)(43). The Pro5 cell line allows normal CHO cell protein sialylation, whereas Lec2 cells, deficient in the CMP-sialic acid transporter, produce proteins that are essentially nonsialylated.…”
Section: Table Imentioning
confidence: 99%